Aggregate Evolution Mechanism during Ion-Adsorption Rare Earth Ore Leaching. (21st November 2018) - Zhao, Kui; Zhuo, Yulong; Wang, Xiaojun; Zhong, Wen
Abstract : The phenomenon of particle aggregation occurs when ammonium chloride is used as a leaching reagent to infiltrate rare earth samples. To reveal the formation and evolution mechanisms of aggregates, a self-developed column leaching experimental device was employed in conjunction with nuclear magnetic resonance technology. The relationships among the amount of rare earth leaching, the evolution of the microscopic pore structure, the porosity, and the leaching time were obtained. A comparative analysis of pure water and ammonium chloride test groups revealed that aggregates were present only in the latter. Consequently, the results of comprehensive analyses indicate that the formation of aggregates is a temporary particle deposition phenomenon caused by the settling of fine soil particles migrating from the top to the bottom of a sample. Furthermore, chemical exchanges constitute the main cause of aggregate formation.